Comparative Evaluation Of Fracture Resistance Of Three Different Ceramic Posts In Endodontically Treated Teeth: A Systematic Review (Journal of Pharmaceutical Negative Results, 2022)
Metal posts used to restore endodontically treated teeth may shine through all-ceramic crowns and thin gingival tissue. When nonprecious alloys are used, corrosion products may lead to discoloration. All ceramic posts and cores can be used in combination with all-ceramic crowns to prevent these problems. All-ceramic posts and cores are highly biocompatible and will almost always increase the translucency of an all-ceramic restoration. Hence a prefabricated zirconia ceramic post system has been introduced to satisfy aesthetic needs presented by endodontically treated anterior teeth. The translucency of all ceramic crowns can be successfully maintained with the use of ceramic post and core materials. In the existing published reports, most studies indicate the superiority of ceramic posts in terms of their fracture resistance but very few show the exact comparison and compilation between the fracture resistance of different ceramic posts with one another. The present systematic review aims at synthesizing all the available data. The purpose of this study was to systematically review the existing reports to compare and evaluate the fracture resistance of 3 types of ceramic posts by combining the available evidence in a systematic review. A search strategy was adopted using PubMed, ScienceDirect, and Google Scholar in May 2022 to screen research studies. These studies were screened against predetermined criteria for eligibility for systematic review. The values of fracture resistance to load applied on copy milled, pressable and pre-fabricated zirconia posts showed that the Prefabricated zirconia posts were more resistant to fracture when loads were applied.